ISOLASI DAN PENAPISAN BAKTERI PENGHASIL ENZIM PROTEASE, SELULASE, DAN AMILASE DARI SEDIMEN DAN SALURAN PENCERNAAN TERIPANG HITAM Holothuria atra - Dien Arista Anggorowati; Hendra Munandar; Lisa Fajar Indriana (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Sea cucumber Holothuria atra has potential value as raw material for pharmacy industry that has been cultivated in Research Development Division for Marine Bio Industry – Indonesian Institute of Sciences (LIPI) since 2016. Disease infections and decreased survival rate are one of the obstacles in in this type of sea cucumber cultivation activities especially during broodstock management. One effort to overcome this is the use of probiotic bacteria. This research aims to isolate and select bacteria that produce protease, cellulase, and amylase enzymes as candidates for probiotic bacteria in the sediment and digestive tract of sea cucumber H. atra. The growth of bacteria from sediments and digestive tract on selective media which added cellulose, starch, and casein substrates was carried out to see the potential of bacteria capable of producing cellulase, amylase, and protease enzymes through the hydrolysis process. The two bacterial isolates that had the highest cellulase and amylase enzyme activity were obtained, namely SSe9 isolates with Hydrolysis Capacity 7 mm index and SAm6 isolates with hydrolysis index Capacity 6.6 mm. These results indicate that the two bacterial isolates have the potential to be further developed into probiotic bacteria.